Przesłanki budowy teorii zmian konsumpcji we współczesnej gospodarce polskiej - Żabiński, Leszek (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
In the author's opinion, the present theory of consumption in Polish economy fulfills its explanatory tasks (although not prognostic ones) with respect to pre- -crisis phases of consumption and economic development. However, the said theory, and especially its assumptions, need to be revised if they are to be useful in contemporary studies on variations in consumption processes in Poland. Referring to the fundamental aims and motives of research carried out within the Branch Basic Research Project (RPBP No. III. 39 ("Changes in the Structure of Consumption") the author presents the most important theory — construction assumptions adopted in the synthesis of the above research project. In a socialist system, the long-term optimum level of consumption may not be the aim of economic activity. Instead, such an aim may be the achievement of economic surplus (in the stage of production, exchange and consumption) and maximalization of social utility effect with respect to market-verified outlays. The consumption itself is not only the effect of economic activity but also one of the main productive forces that contribute to the creation of that surplus both during working time as well as during the time off. If so, the consumption may at best be shaped indirectly by means of future models of consumption (which are chosen by consumers through their voting for election platforms of main political groups) and by means of market mechanisms, supported by parametric steering applied until full marketization of the socialist economy is reached. In the future, social consumption, including collective consumption, will remain the main field of that steering. Referring to the reinterpreted principles of the consumption theory in the socialist economy the author confronts them with detailed theoretical assumptions of research in particular subjects of RPBP III 39 project.
Assumptions of constructing the consumption variations theory in contemporary Polish economy